PSEUDO NOUN INCORPORATION IN BATAK TOBA: A MORPHOSYNTACTIC ANALYSIS - Nurianti Sitorus; Mulyadi Mulyadi (Universitas Islam Sumatera Utara (UISU), 2026)
This study investigates the occurrence of Pseudo Noun Incorporation (PNI) in Batak Toba, a phenomenon not previously been analyzed within incorporation frameworks. PNI has been widely described in languages such as Niuean, Sakha, Hindi, and Tamil. The researchers realize that former studies have not examined PNI in Batak Toba. Drawing on two theoretical accounts by Massam (2001) and Baker (2014), this research analyzes morphosyntactic properties such as verb–noun adjacency, reduced nominal structure, and detransitivization. Using a qualitative descriptive approach based on corpus data and native-speaker judgments, the study identifies several PNI characteristics in Batak Toba, including adjacency, non-specific interpretation, restricted modification, and word-order variation. The findings demonstrate that PNI in Batak Toba aligns with cross-linguistic patterns while also exhibiting language-specific constraints, particularly in the absence of overt case marking. The present study fills and investigates the gap in which PNI in Batak Toba is possibly materialized. This study employs a descriptive qualitative method to systematically describe PNI as it occurs naturally. The data were obtained from naturalistic corpus data and relevant literatures. It is done to ensure empirical validity and grammatical reliability. The findings indicate that Batak Toba displays several characteristics of PNI, including adjacency and verb detransitivization. Furthermore, modified nominals, conjoined nominals, and changes in word order are also observed. Overall, this study offers the first systematic description of PNI in Batak Toba and contributes to broader typological and theoretical discussions of pseudo incorporation.